Modelling the Dynamic Effects of Elective Hospital Admissions on Emergency Levels in England - Sergi Jiménez-Martín; Catia Nicodemo; Stuart Redding (Institute of Labor Economics (IZA), 2019)
In England as elsewhere, policy makers are trying to reduce the pressure on costs due to rising hospital admissions by encouraging GPs to refer fewer patients to hospital specialists. This could have an impact on elective treatment levels, particularly procedures for conditions which are not life-threatening and can be delayed or perhaps withheld entirely. This study attempts to determine whether cost savings in one area of publicly funded health care may lead to cost increases in another and therefore have unintended consequences by offsetting the cost-saving benefits anticipated by policy makers. Using administrative data from Hospital Episode Statistics (HES) in England we estimate dynamic fixed effects panel data models for emergency admissions at Primary Care Trust and Hospital Trust levels for the years 2004–13, controlling for a group of area-specific characteristics and other secondary care variables. We find a negative link between current levels of elective care and future levels of emergency treatment. This observation comes from a time of growing admissions and there is no guarantee that the link between emergency and elective activity will persist if policy is effective in reducing levels of elective treatment, but our results suggest that the cost-saving benefits to the NHS from reducing elective treatment are reduced by between 5.6 per cent and 15.5 per cent in aggregate as a consequence of increased emergency activity.
Keywords: I10; I14; C10; B12; 330; emergency; hospital admissions; elective; NHS